2014
DOI: 10.1542/peds.2013-2309
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Prevalence of Developmental Delay in Young Children With Congenital Heart Disease

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Children with congenital heart disease demonstrate a high prevalence of low-severity developmental problems in the areas of language, motor skills, attention, and executive function. Systematic evaluation has been recommended to promote early detection of problems and ensure appropriate intervention. WHAT THIS STUDY ADDS:This study presents results of longitudinal testing in early childhood. Developmental delays were common. Feeding difficulty and medical and genetic comorbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
190
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(202 citation statements)
references
References 22 publications
9
190
2
1
Order By: Relevance
“…However, despite this increased survival, a high risk for neurodevelopmental co-morbidity persists [2]. Neurodevelopmental outcomes are characterized by a diverse spectrum of developmental delays and disabilities including impaired executive functions with the prevalence and severity increasing with the complexity of the CHD [3][4][5][6][7]. The etiology of these neurodevelopmental disorders is complex and several variables including pre-existing brain abnormalities and evolving factors in the perioperative period are believed to play a significant role [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this increased survival, a high risk for neurodevelopmental co-morbidity persists [2]. Neurodevelopmental outcomes are characterized by a diverse spectrum of developmental delays and disabilities including impaired executive functions with the prevalence and severity increasing with the complexity of the CHD [3][4][5][6][7]. The etiology of these neurodevelopmental disorders is complex and several variables including pre-existing brain abnormalities and evolving factors in the perioperative period are believed to play a significant role [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] In the postnatal period, hypoxia, decreased cardiac output or altered circulation patterns, exposure to cardiopulmonary bypass and circulatory arrest, risk of stroke, polycythemia, and prolonged hospitalizations can contribute to the neurodevelopmental morbidity seen in these children. 4,5,7,8,18,19 In addition, genetic vulnerabilities frequently coexist with CHD, such as the association with the Apolipoprotein E є2 genotype. 20 Early research into improving neurodevelopmental outcomes in children with CHD focused on modifiable perioperative risk factors.…”
mentioning
confidence: 99%
“…There is significant variability in the degree of developmental impairments, which include impairments in fine and gross motor skills, visual-spatial skills, executive functioning, social cognition, and memory, all of which can affect overall academic achievement and longterm quality of life. [3][4][5][6][7][8][9][10][11] The reasons that children with CHD are at risk for neurodevelopmental problems are multifactorial and include genetic factors, as well as prenatal and postnatal physiology and deleterious postnatal exposures. 5,8,12 Preoperative brain imaging studies in patients with cardiac defects characterized by altered cerebral blood flow and oxygen content reveal reduced brain volume and delayed brain maturation, which increases susceptibility to white matter injury and is reminiscent of the encephalopathy of prematurity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several outcome studies of patients with congenital heart disease showed that, in early childhood, motor development seems to be more affected than cognitive development [137,138] . This seems to change when the child gets older, with improvements in motor scores, behavioural problems, and learning difficulties [139] . Data on the long-term consequences of restrictive oxygen supplementation until school age is lacking.…”
Section: Therapeutic Approachesmentioning
confidence: 99%